Benefits of Well‐Being Training in Healthy Older Adults. Issue 3 (6th September 2017) - Cantarella, Alessandra; Borella, Erika; Marigo, Cinzia; De Beni, Rosanna
Abstract : Introduction: Several studies have shown that psychological well‐being (PWB) can be promoted through positive psychological interventions (PPIs). Although these interventions have shown promising results in clinical settings, only a few studies have investigated their effectiveness in older adults, and they have rarely considered an active control group. In addition, generalisation effects of the PWB training to quality of life (QoL) and to untrained cognitive abilities have never been considered. Objective: In this study, we evaluated the effectiveness of a six‐session PWB intervention aiming specifically to improve PWB, and sought any transfer effects on an aspect related to PWB, QoL. Transfer effects on a high‐level cognitive process, working memory (WM), were also investigated. Methods: Thirty‐two older adults (61–82 years old) volunteered to take part in the study and were randomly assigned to either a training group or an active control group. Results: Only the trained group, once controlled for variability, reported larger gains in PWB and in WM performance after the training. Conclusions: This pilot study suggests that PWB training can be effective in older adults, with a positive generalisation effect on cognition (WM). The discussion focuses on the need to develop PPIs tailored to older adults' needs and resources.